2002
DOI: 10.1136/vr.151.7.206
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Actinobacillus pleuropneumoniae serovars 2, 3 and 9 in slaughter pigs from Belgian fattening farms

Abstract: Fifty randomly selected fattening pig herds were studied to investigate the epidemiological characteristics of infections with Actinobacillus pleuropneumoniae serovars 2, 3 and 9, and to identify risk factors for their within-herd seroprevalences. Information about 13 farm characteristics was obtained by means of a questionnaire and used to assess potential risk factors for the percentage of slaughter pigs with antibodies against each of the three serovars. The presence of antibodies was measured with an indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Often, subclinically and chronically infected animals do not show any clinical symptoms. As App is commonly endemic in pig populations, antibody detection by serological tests does not enable discrimination between subclinical infection and disease [12-15]. …”
Section: Introductionmentioning
confidence: 99%
“…Often, subclinically and chronically infected animals do not show any clinical symptoms. As App is commonly endemic in pig populations, antibody detection by serological tests does not enable discrimination between subclinical infection and disease [12-15]. …”
Section: Introductionmentioning
confidence: 99%
“…Actinobacillus pleuropneumoniae serotype 2, which was responsible for the clinical outbreak in this herd, is highly prevalent in Belgium (Maes et al., 2000), and also in many other countries (Inoue et al., 1984; Marsteller and Fenwick, 1999). Field observations suggest that biotype 1 serotypes 1, 5, 9 and 10 are more virulent than the other biotype 1 serotypes (Haesebrouck et al., 1997).…”
Section: Discussionmentioning
confidence: 95%
“…These relationships are well documented in the literature. Previously, Maes et al (2002) and Mouricout (2004) have shown the infl uence of stall construction on epidemiological status. Thrusfi eld (2005), in his monumental work, demonstrated the decisive infl uence of veterinary strategy on epidemiological status of pig breeding units.…”
Section: Discussionmentioning
confidence: 99%